Democracy is Health While Totalitarianism is a Disease: A Study of George Orwell’s 1984: Exploring the Dark Realities of Totalitarianism in George Orwell's 1984 (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The object of this Research Paper is to make the people aware of the fatal results ofTotalitarian government which denotes terror, horror, and dominance of man over man, where we cansee the death of individual freedom. 1984 is always referred to as one of the frightful and horrifying textsof the modern dystopian literature. George Orwell boldly criticized the Totalitarian government. Orwelltried to show the real picture of Totalitarian government in any state, through this dystopian novel 1984.There is a character, Big Brother who controls the whole state and whatever he wants to do, he can dobecause nobody can oppose him if anyone tries to live according to his own desires and freedom,definitely he shall be punished to death. And the most dangerous thing is that, everyone has to love BigBrother with the expression of happiness at the end even they know that he is a cruel dictator.